National Health Interview Survey, 1996: Health Insurance Supplement ([Verlag nicht ermittelbar], 1999)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1996 [ICPSR 2661]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The 1996 Health Insurance questionnaire was administered throughout the full year with the exception of the last three weeks of December. Respondents answered for all members of the household. Variables included in the supplement cover type of health care coverage (Medicare, Medicaid, military/CHAMPUS/CHAMP-VA, public assistance, private insurance), characteristics of the private insurance reported by the respondent (choice of doctor, source of coverage, employer subsidies for premiums, fee-for-service plans, Health Maintenance Organization [HMO] status, HMO type, HMO enrollment size, plan code list), and individual coverage status. Also covered were problems concerning denial or restriction of coverage, "job lock" due to insurance, reasons household members were not covered by insurance (either currently or within the past year) and for how long, and out-of-pocket expenses in the past year for medical services not covered.